Perkembangan Asuransi Syariah di Indonesia Ditinjau dari Pertumbuhan Eksponensial - Ulil Absor Faiq Abdillah; Mugiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine the six exponential processes experienced by Islamic insurance companies in Indonesia. The research method used is qualitative method. This research uses a literature approach sourced from books, journals and articles that are in accordance with the topic and focus of the research. The literature study method is used in this research to find scientific and theoretical studies. The analysis technique used uses the concept of exponential growth which consists of six stages. The results of this study show that sharia insurance in Indonesia has gone through exponential stages similar to technological developments in other industries. Six stages such as digitalization, deception, disruption, dematerialization, demonetization and democratization have adopted technology and found new ways to integrate those innovations into the business, allowing to increase efficiency, lower costs, and provide added value to customers. PT Asuransi Jasindo Syariah is one of the sharia insurance companies in Indonesia that shows a significant increase to reach the democratization stage, because it is not only a sharia insurance application, but there are many choices of features other than insurance such as several Islamic articles, sadaqah features and the implementation of cash waqf.